THU0653-HPR BARRIERS FOR THE UPTAKE OF EULAR POSTGRADUATE EDUCATION FOR HEALTH PROFESSIONALS IN RHEUMATOLOGY IN EASTERN EUROPEAN COUNTRIES: RESULTS FROM 3 NATIONAL SURVEYS. (2nd June 2020) - Van Bodegom-Vos, L.; Vliet Vlieland, T. P. M.; Carmona, L.; Damjanov, N.; Domjan, A.; Goehmann, A.; Iagnocco, A.; Kosanovic, M.; Moe, R. H.; Peter, W.; Segrt, M.; Tonga, E.; et al.
Abstract : Background: Health professionals play an important role in the care for people with rheumatic and musculoskeletal diseases. In order to improve and maintain the quality of their work, appropriate professional education is needed. EULAR has developed several educational products and activities specifically targeted at Health Professionals in Rheumatology (HPR), but particularly in Eastern European countries, their uptake is limited. The overarching aim of a EULAR project (named HEE4ALL: Health professionals Education in Eastern European countries for All) is to develop and execute implementation strategies for EULAR educational activities in 3 eastern European countries. Objectives: The aim of the present analysis was to identify barriers and facilitators for the uptake of EULAR educational activities among HPR in Eastern European countries. Methods: First, a questionnaire was sent to representatives of national health professionals' or patients' organization in 17 Eastern European countries, in order to determine their eligibility to participate in the implementation project. Eligibility criteria were: Having a national HPR organization; Willing and able to compose a team with HPR, Patients, and Rheumatologists; and Interested to participate in the project. Selected countries (minimum 3) were requested to set up a national implementation team, and conduct a national, electronic survey among HPR on anticipated barriers and needs regarding educational activities. The survey included the following elements: a. characteristics of the responding HPRs; b. Familiarity with EULAR educational offerings; c. Anticipated barriers and facilitators (score 0=no barrier at all to10 very important barrier); d. Ability to pay for the HPR online course. Results: Representatives from 10/17 Eastern European countries responded to the first questionnaire, with 3 countries meeting the selection criteria: Hungary, Serbia and Turkey. Subsequently, 216 (H:106, S:42 and T:68) HPR completed the 3 national surveys. In all 3 countries, the majority of the respondents was female (93.1%), and nurse (70.8%) or physical therapist (19.0). Familiarity with EULAR educational offerings was poor, with the lowest proportions of HPR being familiar with postgraduate face-to-face courses (13.9%), educational visits (19.0%) and the EULAR online course for HPR (25.0%). The highest ranked barriers in all 3 countries included the costs of EULAR annual congress, the costs of the EULAR HPR online course and a lack of mastery of English language.The maximum amount of money HPR were able to pay for the EULAR online course was on average €66, €29 and €83 in Hungary, Serbia and Turkey, respectively. Conclusion: Based on a survey in 3 Eastern European countries, it appears that familiarity with EULAR educational offerings is suboptimal. However, when HPR are aware of the educational offerings, their costs and a lack of mastery of the English language seem to be the most important barriers for participation. Based on these results, the 3 national teams developed implementation plans during a 2-day meeting (October 2019). The implementation plans are now executed and a process and effect evaluation is planned by November, 2020. Acknowledgments: Supported by EULAR; Project HPR 042 Disclosure of Interests: Leti van Bodegom-Vos: None declared, T.P.M. Vliet Vlieland: None declared, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution), Nemanja Damjanov Grant/research support from: from AbbVie, Pfizer, and Roche, Consultant of: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Speakers bureau: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Andrea Domjan: None declared, Alzbeta Goehmann: None declared, Annamaria Iagnocco Grant/research support from: Abbvie, MSD and Alfasigma, Consultant of: AbbVie, Abiogen, Alfasigma, Biogen, BMS, Celgene, Eli-Lilly, Janssen, MSD, Novartis, Sanofi and Sanofi Genzyme, Speakers bureau: AbbVie, Alfasigma, BMS, Eli-Lilly, Janssen, MSD, Novartis, Sanofi, Marija Kosanovic: None declared, Rikke Helene Moe: None declared, Wilfred Peter: None declared, Marija Segrt: None declared, Eda Tonga: None declared, Codruta Zabalan: None declared